Correlates of non-adherence to antiretroviral therapy in a cohort of HIV-positive drug users receiving antiretroviral therapy in Hanoi, Vietnam. (August 2014) - Jordan, MR; Obeng-Aduasare, Y; Sheehan, H; Hong, SY; Terrin, N; Duong, DV; Trung, NV; Wanke, C; Kinh, NV; Tang, AM
The HIV epidemic in Vietnam is concentrated, with high prevalence estimates among injection drug users and commercial sex workers. Socio-demographics, substance use and clinical correlates of antiretroviral therapy non-adherence were studied in 100 HIV-1 infected drug users receiving antiretroviral therapy for at least 6 months in Hanoi, Vietnam. All study participants were men with a mean age of 29.9 ± 4.9 years. The median duration on antiretroviral therapy was 16.2 ± 12.7 months; 83% reported 'very good' or 'perfect' adherence in the past 30 days on a subjective one-item Likert scale at time of study enrollment; 48% of participants reported drug use within the previous 6 months, with 22% reporting current drug use. Injection drug use with or without non-injection drug use in the past 6 months (95% C.I. 2.19, 1.30–3.69) and years on antiretroviral therapy (95% C.I. 1.43, 1.14–1.78) were correlated with suboptimal adherence. These findings support Vietnam's ongoing scale-up of harm reduction programmes for injection drug users and their integration with antiretroviral therapy delivery. Moreover, results highlight the need to identify and implement new ways to support high levels of antiretroviral therapy adherence as duration on antiretroviral therapy increases.